1996
DOI: 10.1055/s-2007-972831
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Comparison of RPE During Variable and Constant Exercise Protocols Performed by Older Women

Abstract: The purposes of this study were to assess if women 60 to 75 years of age perceived a series of exercise intensities differently from selected intensities in that series and to determine if a particular intensity was perceived more reliably. Twenty-four women (65 +/- 3.8 yr) completed a walking VO2max treadmill test. Subjects were either assigned to a variable, randomly ordered exercise protocol (GP1) or to one of three constant exercise protocols (Gps2-4). Each subject performed relative exercise intensities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 2 publications
0
10
0
3
Order By: Relevance
“…This concurs with other studies which have shown that cumulative effect contributes to increases in perceived exertion. 38 …”
Section: Perceived Exertion and Relation To Hr During Walk Testsmentioning
confidence: 99%
“…This concurs with other studies which have shown that cumulative effect contributes to increases in perceived exertion. 38 …”
Section: Perceived Exertion and Relation To Hr During Walk Testsmentioning
confidence: 99%
“…Moreover, some studies have established the reliability (or repeatability) of RPE under repeated testing conditions using different kinds of procedures [6,22,28,29,33]. The reliability of RPE has been found to be high in many investigations [10,16,28,29,33]. However, all these studies took place in the laboratory and most were carried out with women [6,16,29,33], or sedentary subjects [16,28,29,33].…”
mentioning
confidence: 99%
“…A amostra total de participantes (somatório de todos os estudos) foi de 426 indivíduos, sendo 333 adultos (média (DP): 31,3 (5,81) anos), sendo 128 homens e 205 mulheres e apenas 93 idosos sem condições especiais de saúde (70,1 (4,05) anos), sendo 16 homens e 77 mulheres. Dos 14 artigos analisados, somente 3 estudos utilizaram a população de idosos [21][22][23] . Os 14 artigos incluídos na revisão abrangeram os anos de 1976 a 2015.…”
Section: Resultsunclassified
“…As modalidades de exercícios utilizados nos estudos foram ciclo ergômetro (38%) 21,23,25,[27][28][29] , esteira (19%) 22,24,26 , exercícios resistidos (13%) 24 , ciclismo indoor (19%) 30,31,32 , jogos no Nintendo Wii (6%) 33 e ciclo ergômetro adaptado para piscina (6%) 24 . Dentre os protocolos utilizados nos artigos, quatro estudos aplicaram protocolos de teste com carga incremental (25%), um estudo aplicou carga decremental (6%), quatro estudos aplicaram carga contínua (25%) e sete estudos aplicaram carga intervalada (44%).…”
Section: Resultsunclassified
See 1 more Smart Citation